PEMBELAJARAN BERDASARKAN MASALAH MATERI GEOMETRI NON EUCLIDES UNTUK MELATIHKAN BERPIKIR KRITIS DAN KREATIF - Fatriya Adamura; Titin Masfingatin; Elma Puspita Kirbiana (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2016)
Development and experiment research have been done because there is no learning tools of problem based learning. Development research was done by using modified 4-D model that consists of define, design, and develop. Research subject is student in Mathematics Education programme of IKIP PGRI Madiun even semester 2013/2014 that is learning Geometry System. Research instrument were validation sheet, reading validation sheet, learning management observation by lecturer sheet, student activity observation sheet, test, and questionnaire. Analysis is done for data that is gotten by research instrument. Summary of the research is good problem based learning tools was developed using modified 4D model. It because validator said that learning tools valid and fulfill criteria: (1) student activity was effective, (2) lecturer capability for learning management was good, (3) test was sensitive, valid, and reliable, (4) student response was positive. Problem based learning tools that is gotten were lesson plan, student worksheet, and test. Problem based learning tools can be used for teaching Non Euclidean Geometry subject because (1) classical student learning completeness fulfilled, (2) student activity in the learning activity fulfill ideal time, (3) lecturer capability in the learning management was good, (4) student response for learning tools and activity was positive.